Pelatihan Kader Cilik Lingkungan di SD Negeri 3 Bangelan, Dusun Sidomulyo, Desa Bangelan, Kec. Wonosari, Kab. Malang (TEKAD : Teknik Mengabdi, 2025)
Village development does not only focus on improving the welfare and quality of life of the community, but also on sustainable use and management of the environment. Creating a clean environment is the obligation of various parties. However, the problem of environmental cleanliness is still an obstacle, which is caused by a lack of public awareness about clean and healthy living behavior, one of which is throwing rubbish carelessly. Littering can reduce environmental quality and cause serious problems if not addressed. Bangelan Village has natural tourism potential that requires maintenance to maintain the beauty of this tourism. One strategy for maintaining the beauty of tourism is to accustom people to clean and healthy living habits, especially through getting village children accustomed to throwing away rubbish and sorting it according to type. This habit is expected to be a form of strategy for character education, awareness and the ability to be more sensitive to the surrounding environment, especially for students at SD Negeri 3 Bangelan. Students who previously only threw rubbish carelessly are expected to become more sensitive to their environment and utilize rubbish into useful items. The aim of this training is to increase the awareness of the Bangelan Village community about clean and healthy living behavior, with a focus on forming a Little Environmental Cadre through training in 3R waste sorting and organic waste processing.